GAMBARAN TINGKAT PENGETAHUAN HIPERTENSI DAN PENCEGAHANNYA PADA LANJUT USIA DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA 2 CENGKARENG - Emil, Emil (Jurnal Nurse, 2020)
Knowledge is the result of knowing and occurs after people have sensed a certain object. Hypertension causes high mortality and morbidity. In order to avoid complications of hypertension patal, good precautions must be taken, keeping the foods that are allowed and not allowed. Old age is a natural process that cannot be avoided. There were 18 (11.2%) people who had a stroke and 38 (23.7%) people who fell at the Tresna Werdha social institution. This study aims to describe the level of knowledge of hypertension and its prevention in the elderly at the Tresna Werdha social institution. The research design used is simple descriptive. The sampling technique was simple random sampling, the number of samples was 62 respondents. The place of research is the Tresna Werdha social institution. The results showed that the most elderly people in the age category 70-79 years were 24 people (34.8). The most gender category is female 41 people (59.4%). The highest education category is SD 33 people (47.8%), the category with the lowest level of knowledge is 48 people (69.6%). The category of hypertension prevention efforts is 38 people ( 55.1%). Â  Â